Artistic licence: artwork permission practices at The Lancet group - Danielle S. Gash; Christopher H. Wortley (European Science Editing, 2023)
Artwork within publications, broadly covering non-text items including graphs, diagrams, and photographs, is typically published under a copyright licence, and permission for the reproduction of such items needs to be sought. The various image rights can be difficult to navigate, especially in the era of open access, and thus at The Lancet, we have developed a streamlined workflow to guide our teams on artwork permission processes in our journals. We present a practical guide for other publishing professionals, which can be adapted to meet their resources and needs.